The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3988/jcn.2021.17.4.558
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of Straight Head Hanging in Posterior Canal Benign Paroxysmal Positional Vertigo

Abstract: Background and Purpose To determine the diagnostic value of straight head hanging (SHH) in benign paroxysmal positional vertigo involving the posterior semicircular canal (PC-BPPV). Methods We retrospectively included 62 patients (age=56.2±15.0 years, 47 female) with unilateral PC-BPPV who underwent both the Dix-Hallpike maneuver and SHH before receiving canalith repositioning therapy (CRT) between September 2017 and July 2020 at the Dizziness Center of Seoul National U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…In fact, the intensity of nystagmus triggered by positional tests depends on the number, size, density of the otoliths, the angle between the semicircular canal plane and the direction of gravity, the moving distance of otolithic debris, the angular acceleration and the amplitude of head motion during the positional tests ( 19 , 20 ). Some scholars reported that they employed SRT alone to identify the affected side of HSC-BPPV, and its accuracy rate was 62% ~ 75% ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the intensity of nystagmus triggered by positional tests depends on the number, size, density of the otoliths, the angle between the semicircular canal plane and the direction of gravity, the moving distance of otolithic debris, the angular acceleration and the amplitude of head motion during the positional tests ( 19 , 20 ). Some scholars reported that they employed SRT alone to identify the affected side of HSC-BPPV, and its accuracy rate was 62% ~ 75% ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the SPV of nystagmus evoked by the position tests is not only related to the skills of the technicians, the angle between the semicircular canal plane and the gravity vector during the position movement, and the distance that the otolith fragments move ( 23 , 24 ), but also to the number, size and density of the otolith particles ( 25 ). Larger or heavier otolith particles may lead to higher SPV of nystagmus evoked by the position tests.…”
Section: Discussionmentioning
confidence: 99%
“…Even though the Dix-Hallpike maneuver remains the gold-standard positioning maneuver for diagnosing PC-BPPV, SHH also evokes the typical positional nystagmus observed in PC-BPPV. 3 In unilateral PC-BPPV, the induced nystagmus would be ipsiversive torsional and upbeat during SHH owing to the otolithic debris migrating away from the ampulla and resultant stimulation of the involved PC. 3 In bilateral PC-BPPV, the induced nystagmus would be mostly upbeat when both PCs are symmetrically affected due to the opposing torsional components being canceled out.…”
mentioning
confidence: 99%
“… 3 In unilateral PC-BPPV, the induced nystagmus would be ipsiversive torsional and upbeat during SHH owing to the otolithic debris migrating away from the ampulla and resultant stimulation of the involved PC. 3 In bilateral PC-BPPV, the induced nystagmus would be mostly upbeat when both PCs are symmetrically affected due to the opposing torsional components being canceled out. 4 However, the torsional component in our patient changed from counterclockwise to clockwise, while the upbeat nystagmus remained unchanged.…”
mentioning
confidence: 99%